Hubungan Antara Konsep Islam Wasathiyah dan Pancasila dalam Penerapan Kehidupan Berbangsa dan Bernegara di Indonesia - Kurniawan, Bhagaskoro Ardhianto; Tiana, Ella Aprilia; Ma'ruf, Nirwanto (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Indonesia there are now many groups that act in the name of Islam for certain interests and think that our country's ideology is wrong. Anakri's attitude is shown in various places. And this research will examine and answer that the concept of Islam wasathiyah is very in line with Pancasila and is very relevant in its implementation in this nation. This research uses qualitative methods by conducting a literature review. Researchers look for data and information from previous research that is related to the topic to be researched. This research aims to find out how the concepts of Islam wasathiyah and Pancasila are in the life of the nation and state in Indonesia. The results of this research show that the concept Islam wasathiyah is in harmony with Pancasila in national and state life. There are similarities between the concept of Islam wasathiyah and the contents of Pancasila, how in Indonesia there is diversity, namely diversity but still one and the concept of Islam wasathiyah which upholds harmony in religion